Rola instytucji pozarządowych w opiece nad dzieckiem na Pomorzu Środkowym w latach 1945–1975 – zarys problemu - Apanel, Danuta (Biuletyn Historii Wychowania, 2009)
The activity of NGOs in Middle Pomerania after the end of WWII to the times of political changes and economic transition can be divided into two characteristic and distinct stages, i.e. one until the year 1950, and the other covering the years from 1950 to the political breakthrough of 1989. In the first stage, the activities directed at well-being of the child and the family were mostly undertaken by the Worker’s Society of the Friends of Children (Polish: RTPD), the Peasants’ Society of the Friends of Children (ChTPD), Polish Red Cross (PCK), Central Committee for Welfare (CKOS), the Polish Women League and the Society for Pupils’ Hostels and Scholarships. The above organizations kept sanitary and medical facilities, educational and care institutions, including children’s homes, correctional houses, preventoria, day care rooms, pupils’ hostels and boarding houses, crčches and kindergartens, ran summer camps for children, field kitchens, hospitals, night shelters, training workshops, catering establishments, outpatient clinics, ambulance services, health care establishments and mother and child care units. According to the data available at the archives of the Society of the Friends of Children in Koszalin covering the years 1946–1949, included in annual reports of RTPD and ChTPD, these organizations provided care to about 8,300 children CKOS attended to about 43,500 individuals, including children. The organization distributed clothing, footwear and medicine obtained within the framework of the structural assistance from the UN. According to data obtained from annual reports of the Polish Red Cross in Koszalin for the years 1945–1955, assistance was rendered to about 120,000 individuals. Towards the end of the first stage of the activity of NGOs, due to the changes in welfare policy of the country, many organizations were dissolved or had to change their profile. The most successful organization in the second stage was the Society of the Friends of Children. The Society provided social and vocational counseling services, ran day care rooms, kindergartens, village crèches, summer camps for children and summer and winter play centres. The available reports of regional TPD in Middle Pomerania for the years 1950–1975, state that there were 322 local associations of TPD in the region, amounting to 10,570 members. Work of NGOs in Middle Pomerania was basically determined by the long-run process of assimilation of the population that came from other regions of the country to new living conditions, by considerable war damages and lack of stability and security.